Formulasi sediaan garam mandi dengan penambahan pewarna alami kopigmentasi kesumba keling (Bixa orellana L.) dan angkak merah - Salman Salman; Agustina Magdalena; Sudewi Sudewi; Meutia Indriana (Journal of Pharmaceutical and Sciences, 2023)
Background; Annato seeds and red yeast rice contain carotenoids and anthocyanins as natural dyes so that they can replace synthetic dyes. This study aims to determine the copigmentation of annatto seeds and red yeast rice in the form of ethanol extract which can be formulated as a natural dye into salt bath preparations. Methods; Annatto seeds and red yeast rice were macerated using 96% ethanol. Making formulations in concentrations of 3%, 6% and 9%. Then the preparation evaluation test was carried out which included the pH test, water content test, dissolution time test, moisture test and irritation test. Result; The yield of annatto seeds and red yeast rice was 8.65% and 11.19%, respectively. The preparation of copigmented bath salts of annatto seeds ethanol extract with red yeast rice is a preparation that has a pH range of 7.4-7.5, with a dissolving time of under 5 minutes. The preparation of copigmented bath salts with the ethanol extract of annatto seeds and red yeast rice with a concentration of 6% (F2) is a preparation containing a water content of 13.5% and a humidity of 58.8% including the "moist" category. the results of testing on volunteers showed that salt bath from copigmentation of annatto seeds and red yeast rice did not cause irritation